(untitled) (BioMedical Research in Microbiology (BMR Microbiology) (ISSN: 2349-4603), 2024)
This study aimed to isolate the bioluminescent bacterial strains from seawater and sediments in near the Roach Park, coastal area of Tuticorin. Further to identify the luminescent bacteria strains and to screen for production of bioactive metabolites and their bioactivity against human bacterial pathogens. Bioluminescent bacteria are wide spread in natural environment. Water and sediment samples were collected from nearby mangrove ecosystem of the Roach Park off Tuticorin coast, Bay of Bengal. The luminous bacteria density was found to be 3 X 104 CFU/ml - 5 X 104 CFU/g in seawater and sediment respectively. Totally 10 luminescent bacterial strains were identified up to genus levels were selected and screened for the production of antibacterial substance, in the preliminary screening the strains SWLB3, STLB5 and STLB6 strains had shown broad spectrum activity against the human pathogens. Among these strain STBL5 exhibited predominant activity against human bacterial pathogens. The bioactive bacterial metabolites which showed higher activity against human pathogens indicate that luminescent bacteria could be used as a good source for the isolation of bioactive compounds